Advanced density-based methods for the characterization of materials, binding events, and kinetics. (29th September 2022) - Doan-Nguyen, Thao P.; Crespy, Daniel
Abstract : Investigations of the densities of chemicals and materials bring valuable insights into the fundamental understanding of matter and processes. Abstract : Investigations of the densities of chemicals and materials bring valuable insights into the fundamental understanding of matter and processes. Recently, advanced density-based methods have been developed with wide measurement ranges ( i.e. 0–23 g cm −3 ), high resolutions ( i.e. 10 −6 g cm −3 ), compatibility with different types of samples and the requirement of extremely low volumes of sample (as low as a single cell). Certain methods, such as magnetic levitation, are inexpensive, portable and user-friendly. Advanced density-based methods are, therefore, beneficially used to obtain absolute density values, composition of mixtures, characteristics of binding events, and kinetics of chemical and biological processes. Herein, the principles and applications of magnetic levitation, acoustic levitation, electrodynamic balance, aqueous multiphase systems, and suspended microchannel resonators for materials science are discussed.